2016
DOI: 10.1177/0036933015619295
|View full text |Cite
|
Sign up to set email alerts
|

Autologous blood clot embolisation in posttraumatic high-flow priapism

Abstract: Non-ischemic, high-flow priapism is defined as the state of painless and permanent erection of the penis which generally develops by perineal trauma. Selective transarterial embolisation is one of the treatment options. We present an 18-year-old men who had complaints of painless and permanent erection after a blunt perineal trauma. Colour Doppler ultrasound revealed a pseudoaneurysm and fistula at the left cavernosal artery. Hence autologous blood clot injection was performed to embolise the pseudoaneurysm. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…10,15,17 Emin Ozbek et al reported a case of proximal partial priapism which was treated successfully with ABC embolisation 15 Guliz Yilmaz et al reported a case of painless priapism due to PA and fistula of the left cavernosal artery as result of a trauma, which fully recovered by trans-arterial embolisation of ABC. 17 Also in other studies performed with a larger group of patients, this method had the effectiveness of 100%. 15 In 1975, Miller et al reported a successfully treated PA of the internal maxillary artery that resulted in active bleeding, with catheter embolisation of ABC.…”
Section: Discussionmentioning
confidence: 99%
“…10,15,17 Emin Ozbek et al reported a case of proximal partial priapism which was treated successfully with ABC embolisation 15 Guliz Yilmaz et al reported a case of painless priapism due to PA and fistula of the left cavernosal artery as result of a trauma, which fully recovered by trans-arterial embolisation of ABC. 17 Also in other studies performed with a larger group of patients, this method had the effectiveness of 100%. 15 In 1975, Miller et al reported a successfully treated PA of the internal maxillary artery that resulted in active bleeding, with catheter embolisation of ABC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to be effective of autologous clot embolisation in the treatment of high‐flow partial priapism in the literature (Akpinar & Yilmaz, ; Cantasdemir et al, ). Here, we treated our patient with autologous clot using superselective transcattheter embolisation.…”
Section: Discussionmentioning
confidence: 99%
“…Although reabsorbable materials have traditionally been the most commonly used, the choice of embolic agent remains inconsistent [6,13] including autologous blood clot [14], gelatin sponge particles, polyvinyl alcohol [15], coils and N-butryl cyanide (NBCA) [6,14], and Ethylene-vinyl alcohol copolymer (Onyx®) [3]. Autologous blood clot, a temporary occlusive agent, is very effective for treatment of high-flow priapism and permits restore normal blood flow after absorption [5,6,14,16,17]. Lloret et al describe two cases of patients with high flow priapism treated by using non-reabsorbable materials of microcoil embolization [12].…”
Section: Discussionmentioning
confidence: 99%